A methodological project for the automatic selection of descriptors for digitized texts using noun phrases - Souza, Renato Rocha; Alvarenga, Lidia (Proceedings of the Brazilian Symposium in Information and Human Language Technology (STIL); 2004: Proceedings of the 2nd Workshop in Information and Human Language Technology, 2004)
It can be noticed that the indexing and representation strategies nowadays seems to be near the exhaustion, and it is worth to investigate new approaches to the indexing and information retrieving systems. Among these, a branch tries to consider the intrinsic semantics of the textual documents using noun phrases as descriptors instead of single keywords. We present in this article a methodology that is being developed in the scope of a doctorate research.